Effects of Nitrogen Fertilizer Ratio on Microbial Diversity of Rice Rhizosphere Soil in Cold Region - Chen, Hongwei; Huang, Ling (Cellular and Molecular Biology, 2022)
The experiment was conducted in the paddy field of a scientific and technological park of an agricultural reclamation farm in Xinxiang province from 2017 to 2019. The soil quality of the experimental field was the rhizosphere soil of rice in the cold region, and Longjing 31 was used as the experimental material. The effects of nitrogen application ratio on microbial diversity of rice rhizosphere soil in the cold region were studied. The aim is to provide a theoretical basis for rational fertilization, improving soil environment and high yield and efficiency. The results showed that: (a) the microbial diversity index of rice rhizosphere soil in the cold region was the best after the second nitrogen application; (b) under the ratio of N4 nitrogen application, the activity of bacteria, fungi and actinomycetes in rice rhizosphere soil in a cold region and their survival were the best; (c) under intensive cultivation conditions, the microbial diversity was the highest under SF1 treatment. SF0 treatment had the highest fungal diversity and SF3 treatment had the highest actinomycete diversity. (d) There was no significant effect on the microbial diversity of rice rhizosphere soil in the cold region without nitrogen fertilizer application in a single season.